2016
DOI: 10.1140/epjc/s10052-016-3886-2
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of nonsingular bouncing universes

Abstract: Homogeneous and isotropic, nonsingular, bouncing world models are designed to evade the initial singularity at the beginning of the cosmic expansion. Here, we study the thermodynamics of the subset of these models governed by general relativity. Considering the entropy of matter and radiation and considering the entropy of the apparent horizon to be proportional to its area, we argue that these models do not respect the generalized second law of thermodynamics, also away from the bounce.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…Both instances correspond to small scale systems. Although different authors assumed it to be in order to constrain the evolution of cosmological models (see, e.g., [5] and references therein), as far as we know, the validity of the said law at large (i.e., cosmic) scales has not been explored as yet. The main purpose of this work is to fill this gap.…”
Section: Introductionmentioning
confidence: 99%
“…Both instances correspond to small scale systems. Although different authors assumed it to be in order to constrain the evolution of cosmological models (see, e.g., [5] and references therein), as far as we know, the validity of the said law at large (i.e., cosmic) scales has not been explored as yet. The main purpose of this work is to fill this gap.…”
Section: Introductionmentioning
confidence: 99%
“…The total entropy is sum of horizon entropy (S h ) and the matter (inside the horizon) entropy (S in ) i.e., For an evolving universe it is prudent to consider the entropy of dynamical apparent horizon rather than teleological event horizon. Entropy of the apparent horizon is given by the relation [21][22][23],…”
Section: Compliance Of a Pure Quintessence With Gslmentioning
confidence: 99%
“…where A denotes the area of the apparent horizon and is related to radius of the apparent horizon (R h ) as, A = 4πR 2 h . In a spatially flat FRW space, the horizon radius R h is related to Hubble parameter [21,22,24] as,…”
Section: Compliance Of a Pure Quintessence With Gslmentioning
confidence: 99%
“…Based on the Hubble expansion history, Pavón (2014) suggested that the entropy of the Universe tends to some maximum value. Interestingly different cosmological models such as nonsingular bouncing Universes, modified gravity theories and the Universes whose expansion is dominated by matter or by phantom fields do not tend to a state of maximum entropy whereas the ΛCDM model does (Radicella & Pavón 2012;Mimoso & Pavón 2013;Ferreira & Pavón 2016).…”
Section: Introductionmentioning
confidence: 99%